Role of Adipose Tissue Derived Exosomes in Metabolic Disease - Mei, RuiYan; Qin, WeiWei; Zheng, YanHua; Wan, Zhuo; Liu, Li (Frontiers in Endocrinology, 2022)
Adipose tissues perform physiological functions such as energy storage and endocrine, whose dysfunction will lead to severe metabolic disorders. Accumulating evidences show that exosomes can meditate communications between different tissues by transporting nucleic acids, proteins and other biological factors. More importantly, exosomes secreted by adipose tissue function as critical contributing factors that elucidate specific mechanisms in metabolic disturbance such as obesity, adipose inflammation and diabetes etc. Adipose tissue is the major source of circulating exosomal miRNAs. miRNA secreted from adipose tissues not only altered in patients with metabolic disease, but also result in an increase in metabolic organ talk. Here we have reviewed the latest progress on the role of adipose tissue derived exosomes roles in metabolic disorders. Moreover, the current obstacles hindering exosome-based therapeutic strategies have also been discussed.